2012
DOI: 10.1002/jctb.3719
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic degradation of aqueous Fischer–Tropsch effluents to fuel gas over oxide‐supported Ru catalysts and hydrothermal stability of catalysts

Abstract: BACKGROUND: The catalytic degradation of aqueous Fischer-Tropsch (FT) effluents to fuel gas over Ru/AC has been investigated. In order to understand the catalytic performance and stability of oxide-supported Ru catalysts, several oxide supports (titania, zirconia, γ -alumina and silica) were selected for study, with a focus on the hydrothermal stability of catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, we suggest this property to be of importance for the high activity. Since carbon supports usually possess a superior long‐term stability than Al 2 O 3 in aqueous media, Ru/C was chosen for further optimization of the reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we suggest this property to be of importance for the high activity. Since carbon supports usually possess a superior long‐term stability than Al 2 O 3 in aqueous media, Ru/C was chosen for further optimization of the reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…[35][36][37] Relevant to the present work, Chen et al reported the degradation of oxygenates to hydrocarbons under a H 2 pressure of 98 bar using a Ru catalyst. 38,39 This reaction involves acid-catalyzed dehydration of alcohols and subsequent hydrogenation to paraffins. 40 The reaction mixture in the work of Chen et al was slightly acidic due to the presence of organic acids.…”
Section: Catalytic Activity Measurementsmentioning
confidence: 99%
“…40 The reaction mixture in the work of Chen et al was slightly acidic due to the presence of organic acids. 38,39 To exclude the possibility that the selectivity changes as a function of temperature are caused by secondary reactions of aldehydes and alcohols in the present work, we carried out several additional FT reactions in the presence of decanal. Shorter chain aldehydes could not be used for this purpose because it was not possible to analyze them nor their products in our aqueous-phase FT approach.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%